NANO-CHAMELEONS FOR NSCLC: A REVIEW OF CD-GUIDED IMMUNE CELL-ENGINEERED NANOARCHITECTURES - Dr. Diksha Jindal, S.N Sahoo (JOURNAL OF PHARMACEUTICAL ANALYSIS, 2025)
Non-small cell lung most cancers stays among main reasons of most cancers-related mortality worldwide, with confined powerful healing alternatives because of tumor heterogeneity and immune evasion. Current progress in nanoscience and immune engineering possess enabled the manner for progressive remedy strategies. This review makes a speciality of the improvement and application of nano-chameleons—smart, adaptive nanoarchitectures engineered with immune cells guided with the aid of cluster of differentiation (CD) markers—for targeted remedy in NSCLC. These CD-guided immune cell-engineered nanoarchitectures leverage unique cell focused on, improved tumor infiltration, and immune modulation to conquer conventional healing obstacles. We speak the layout principles, useful mechanisms, and preclinical consequences of such nano-chameleons, highlighting their capacity to enhance specificity, lessen off-goal outcomes, and raise antitumor immune responses. Finally, the review outlines modern challenges and future views in translating those nanoengineered platforms into scientific exercise for personalized NSCLC remedy.